Maximum Power Point Tracking Using DRCC and MRAC With Modified Mit Rules For PV Cells (International Journal of Engineering and Computer Science, 2016)
This paper is about improving the maximum power point tracking by using the Discrete time Ripple Correlation Control and Model Reference Adaptive Control with MIT rules. MPPT technologies have been used in photo-voltaic systems to deliver the maximum power output to the load under changes of solar insolation and solar panel’s temperature. Where as in the existing models combined feature of ripple correlation control (RCC), and the model reference adaptive control (MRAC) are used in Photovoltaic systems to reduce pertabations.This paper includes the  improved version of both RCC and MRAC ,a model two layer architecture which  provides promising increase in tracking efficiency and accuracy. The performance of the pro-posed technique was observed and developed by MATLAB/simulink software.